Optimisation of pelletisation conditions for poplar energy crop - Mediavilla, I.; Esteban, L.S.; Fernández, M.J. (Elsevier, 2012)
Solid biomass usually undergoes a stage of pretreatment with the aim of being prepared for its energy utilisation. Within pretreatment stage, pelletisation process can be considered. Nowadays the main raw materials used for pellets production are wood wastes from sawmills and wood processing industries. However, searching for other raw materials is necessary in order to guarantee the supply. In this work, poplar energy crop has been studied as raw material. The results showed that poplar is a tough material with regard to its pelletisation and maize starch and/or lignosulphonate (a by-product in cellulose production) addition increases the process stability and decreases the specific energy demanded. It has been observed that with maize starch addition, the specific energy demanded during the pelletisation process is lower than with lignosulphonate addition, but, on the other hand, when lignosulphonate is used, physical quality of pellets is higher than with maize starch utilisation. Finally, the optimum conditions found to pelletise poplar are: milling particle size below 4 mm, specific pelletisation surface 5.6 cm2/kW, die compression 26 mm and 4 wt.% (d.b.) of dry additive (3% maize starch plus 1% lignosulphonate).
Accepted version
Keywords: Additive; lignosulphonate; maize starch; pelletisation; poplar